OR21-03 Determining Novel Therapeutic Targets Using an in Vitro Model of TRb Tumor Suppression in Anaplastic Thyroid Cancer - Gillis, Noelle E (J Endocr Soc, 2020)
Anaplastic thyroid cancer (ATC) is one of the most lethal endocrine cancers, with an average survival time of six months after diagnosis. These aggressive tumors are characterized by rapid local extension, distant metastasis, and resistance to radioactive iodine therapy and mainstream chemotherapy. There are very limited treatment options for this aggressive form of thyroid cancer, highlighting a need for a deeper understanding of its mechanisms for development of more effective therapies. Loss of expression of the thyroid hormone receptor beta (TRβ) via epigenetic silencing is common amongst solid tumors, including ATC. Despite its recognized role as a tumor suppressor, the mechanisms underlying TRβ tumor suppressor activity remain uncharacterized. We previously created a stable ATC cell line with constitutive re-expression of TRβ (SW-TRβ). These stable cells exhibit a slower baseline growth rate than both the corresponding parental cell line (SW1736) and the stable empty vector control cell line (SW-EV). Since the effects of thyroid hormone treatment on the growth of cancer cells remain unclear, we investigated changes in growth rates of these cells in response to hormone treatment (triiodothyronine (T(3)) 10(-8)M). While T(3) had no effect on SW-EV cells, the addition of hormone significantly slowed the growth of the SW-TRβ cells after two days. With longer exposure to T(3) (five days), the SW-TRβ cells exhibited an apoptotic phenotype. We confirmed that the observed cell death was due to induction of apoptosis by assessing caspase 3 cleavage by immunoblot. The parental SW1736 cell line harbors a deleterious p53 truncating mutation, which is maintained in our stable cell lines. Therefore, we hypothesize that this T(3)-induced apoptosis is occurring through an alternate, p53-independent, signaling pathway. This prompted us to examine RNA-seq data obtained from these cell lines under similar conditions to identify potential regulators of this response. Interestingly, pathway analysis revealed decreased CDK4/6-mediated cell cycle progression and activation of JAK1/STAT1 signaling upon T(3) treatment. These are novel mechanisms by which activation of T(3)-TRβ signaling can slow tumor growth and promote apoptosis in p53-deficient cancer cells. Furthermore, these pathways represent novel therapeutic targets specifically for ATC with potential high impact clinical applications.